The Benson Relaxation Technique in Reducing Anxiety Levels in Pre-Operative Cataract Patients - Putri Purnama Sari; Jenny Marlindawani Purba; Nunung Febrianty Sitepu (Jurnal Keperawatan Silampari, 2024)
This study aims to determine the effect of the Benson relaxation technique on reducing anxiety levels in pre-cataract surgery patients. The research method uses a quasi-experimental research design. The Wilcoxon test results showed a significant difference in the mean anxiety score between the pretest and posttest in the control group (z=-5.247, p=0.000). In contrast, the Wilcoxon results showed that there was a significant difference in the level of anxiety—mean anxiety value between pretest and posttest in the intervention group (z=-5.518, p=0.000). Mann Whitney U test results showed z=-2.574, p=0.01). In conclusion, there is a significant influence on anxiety scores between the control group and the intervention group. Keywords: Cataract, Preoperative Anxiety, Benson Relaxation